TANTANGAN DAN SOLUSI PEMBELAJARAN DARING DI MASA NEW NORMAL SMA MUHAMMADIYAH KOTA LUBUKLINGGAU - Adinda Mulyani; Afdhal Afdhal (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT This research discusses the Challenges and Solutions of Online Learning in the New Normal Period of SMA Muhammadiyah 1 Lubuklinggau City. The purpose of this study was to determine the challenges and solutions for online learning during the Covid-19 pandemic for teachers at SMA Muhammadiyah 1 Lubuklinggau City. This type of research used in this research is a descriptive type with a qualitative approach. The data collection technique in this research is by using observation, interview and documentation. The informants involved in this study were teachers of SMA Muhammadiyah 1 Lubuklinggau City. The results of this study can be seen that online learning that is implemented for the first time has challenges for teachers both in terms of human resources and facilities / infrastructure. Less proficient in technology, network access and must be creative in implementing this online learning system. So the solutions provided are expected to be able to make online learning interesting, updates in technological developments and provide network access that can simplify the online learning process. Keywords: Online Learning, Challenges, Solutions